Effects of acute ingestion of a pre-workout dietary supplement with and without p-synephrine on resting energy expenditure, cognitive function and exercise performance - Y. Peter Jung; Conrad P. Earnest; Majid Koozehchian; Elfego Galvan; Ryan Dalton; Dillon Walker; Christopher Rasmussen; Peter S. Murano; Mike Greenwood; Richard B. Kreider (Journal of the International Society of Sports Nutrition, 2017)
Background The purpose of this study was to examine the effects of acute ingestion of a pre-workout dietary supplement (PWS) with and without p-synephrine (S) on perceptions of readiness to perform, cognitive function, exercise performance, and markers of safety. Methods In a randomized, double-blind, and counterbalanced manner; 25 healthy and recreationally active male and female participants ingested a flavored maltodextrin placebo (PLA), a PWS containing beta-alanine (3 g), creatine nitrate as a salt (2 g), arginine alpha-ketoglutarate (2 g), N-Acetyl-L-Tyrosine (300 mg), caffeine (284 mg), Mucuna pruiriens extract standardized for 15% L-Dopa (15 mg), Vitamin C as Ascorbic Acid (500 mg), niacin (60 mg), folate as folic acid (50 mg), and Vitamin B12 as Methylcobalamin (70 mg) with 2 g of maltodextrin and flavoring; or, the PWS with Citrus aurantium (PWS + S) extract standardized for 30% p-synephrine (20 mg). Participants had heart rate (HR), blood pressure, resting energy expenditure (REE), 12-lead electrocardiograms (ECG), perceptions about readiness to perform, cognitive function (Stroop Color-Word test), bench and leg press performance (2 sets of 10 repetitions at 70% of 1RM and 1 set to failure), and Wingate anaerobic capacity (WAC) sprint performance determined as well as donated blood samples prior to and/or following exercise/supplementation. Data were analyzed by MANOVA with repeated measures as well as mean changes from baseline with 95% confidence intervals (CI). Results No clinically significant differences were observed among treatments in HR, blood pressure, ECG, or general clinical blood panels. There was evidence that PWS and PWS + S ingestion promoted greater changes in REE responses. Participants reported higher perception of optimism about performance and vigor and energy with PWS and PWS + S ingestion and there was evidence that PWS and PWS + S improved changes in cognitive function scores from baseline to a greater degree than PLA after 1 or 2 h. However, the scores in the PWS + S treatment did not exceed PLA or PWS responses at any data point. No statistically significant differences were observed among treatments in total bench press lifting volume, leg press lifting volume or WAC sprint performance. Conclusions Within the confines of this study, ingestion of PWS and/or PWS + S prior to exercise appears to be well-tolerated when consumed by young, healthy individuals. The primary effects appear to be to increase REE responses and improve perceptions about readiness to perform and cognitive function with limited to no effects on muscular endurance and WAC. The addition of 20 mg of p-synephrine to the PWS provided limited to no additive benefits. Trial registration This trial (NCT02952014) was retrospectively registered on September 13th 2016.